The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.03.04.973487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic prioritization of candidate genes in disease loci identifies TRAFD1 as a master regulator of IFNγ signalling in celiac disease

Abstract: BackgroundCeliac disease (CeD) is a complex T cell–mediated enteropathy induced by gluten. Although genome-wide association studies have identified numerous genomic regions associated with CeD, it is difficult to accurately pinpoint which genes in these loci are most likely to cause CeD.ResultsWe used four different in silico approaches – Mendelian Randomization inverse variance weighting, COLOC, LD overlap and DEPICT – to integrate information gathered from a large transcriptomics dataset. This identified 118… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 76 publications
(118 reference statements)
0
26
0
Order By: Relevance
“…TRAFD1 Is Trans-Regulator in CeD IE-CTL cell lines, Prof. Morris Swertz for data storage and cluster facilities, and Kate McIntyre for editing the manuscript. A preliminary version of this manuscript has been released as a preprint at BioRxiv (Graaf et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRAFD1 Is Trans-Regulator in CeD IE-CTL cell lines, Prof. Morris Swertz for data storage and cluster facilities, and Kate McIntyre for editing the manuscript. A preliminary version of this manuscript has been released as a preprint at BioRxiv (Graaf et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We prioritized CeD-associated genes using three eQTL-based methods-MR-IVW (Burgess and Thompson, 2017), COLOC (Giambartolomei et al, 2014), and LD overlap-and one coregulation-based method, DEPICT (Pers et al, 2015). For the MR-IVW method, we used the independent variants identified by GCTA-COJO as instrumental variables (Yang et al, 2012;Burgess et al, 2013) to test causal relationships between changes in gene expression and CeD, as we have demonstrated that this procedure is preferred over p-value clumping (van der Graaf et al, 2020). MR-IVW was only performed when there were three or more independent eQTLs available (164 genes).…”
Section: Gene Prioritization Using Mendelian Randomization Inverse Variance Weighting Coloc Ld Overlap and Depictmentioning
confidence: 99%
“…Together, these loci and the HLA loci explain more than 40% of the heritability of CeD [ 30 ]. Many of the genes in these loci are immune genes [ 31 ]. Since most of the non-HLA CeD single-nucleotide polymorphisms (SNPs) are located in the non-coding genome, they are likely to contribute to CeD pathology by affecting the expression of genes involved in the biological pathways that are perturbed in CeD.…”
Section: Ced Immunopathologymentioning
confidence: 99%
“…Since most of the non-HLA CeD single-nucleotide polymorphisms (SNPs) are located in the non-coding genome, they are likely to contribute to CeD pathology by affecting the expression of genes involved in the biological pathways that are perturbed in CeD. Although a single SNP might affect only the risk of developing CeD to a small extent, a combination of multiple SNPs and loci may affect downstream central hub genes that could implicate novel biomarkers and therapeutic targets [ 31 , 32 ]. Accompanying the recent publication of data from large case–control genome-wide association studies and population controls, such as the UK biobank, is the now possible ability to calculate genetic risk scores that combine the additive risk of multiple CeD risk-SNPs into one score to indicate the risk of developing CeD [ 10 , 33 , 34 ].…”
Section: Ced Immunopathologymentioning
confidence: 99%
“…More than 95% of the single nucleotide polymorphisms (SNPs) associated with CeD are located in the non-coding genome and presumably deregulate genes important for CeD etiology 27 . Enrichment analysis of the CeD SNPs in regulatory regions suggests that CD4+ T cells are the major cell type affected by genetic risk factors 28 30 . Moreover, pathway and cis -eQTL analyses of genes in CeD loci suggest that they affect T cell receptor (TCR) signaling via alteration of expression of genes such as UBASH3A , CD28 and CSK 30 32 .…”
Section: Introductionmentioning
confidence: 99%